Analisis Kekuatan Mata Pisau Pada Mesin Pengolah Sabut Kelapa - Audia, Ayu; Suhartono, Roni; Ardin, Masri Bin (CV. IRA PUBLISHING, 2025)
The design of a coconut fiber processing machine with a conveyor system requires special attention to the performance of the blade, which serves as the main component in the chopping process. Structural failure of the blade can significantly impact machine efficiency and operator safety. Therefore, modeling and structural strength analysis using computer-aided analysis software was conducted to validate the reliability of the blade design before manufacturing. The study focused on Von Mises stress, displacement, and safety factor, considering operational loads such as bending, torsion, tension, and compression applied to the shaft. The simulation results indicate that both stress and deformation remain within safe limits, with a safety factor value that supports long-term operational use. Based on these findings, the blade design is considered structurally secure and suitable for use in a coconut fiber chopping machine.